Development of a manually operated crane / Muhammad Irsyad Fauzi - Fauzi, Muhammad Irsyad (2024)
Work that needs to be done by people has never been simpler than it is now that machines exist. This project is about designing and fabricating a manually operated crane. Despite the fact that certain crane are more expensive, complicated, large, and immobile. Many people cannot afford a crane due to its high price. Grocery store need to use manually operated crane so that the work done is more efficient and less energy used. The manually operated crane is suitable use for grocery store. It is easy to move around in restricted space. The manually operated crane is smaller in size than other crane. It is using gear and chain for the lifting part. As a result, the goal of this project is to develop and build a machine that is not only portable and affordable, but also compact. This machine can be very useful and affordable for doing heavy work in grocery store. In this project, cutting, drilling, and welding is used to fabricate the manually operated crane. First hang the load to the end of the rope, then we can pull the rope with the handle attached. And finally we can move it around where we want and pull back the load down